Dichapetalaceae endémicas del Perú - León, Blanca (2006)
This family is a recent addition to the endemic Peruvian flora. The Dichapetalaceae are represented in Peru by three genera and 16 species (Brako & Zarucchi, 1993) mostly trees and lianas. Here we recognize one endemic species in the genus Tapura. This endemic species grows in the Humid Lowland Amazonian Forests region at 250 m elevation. It has not yet been recorded in Peru´s protected areas system.